KONSELING MANFAAT PEMBERIAN KOLOSTRUM DAN PEMBERIAN ASI ESKLUSIF PADA BAYI BARU LAHIR DI POSYANDU FLAMBOYAN VI PUSKESMAS KAPASA TAHUN 2023 - Sarina Ali (Jurnal Pengabdian Ilmu Kesehatan, 2023)
According to the 2018 American Pregnancy Association (APA), colostrum is able to form a lining in the baby's stomach and intestines to prevent germs/pathogens from attacking. Helps prevent jaundice in babies by removing residual substances that are harmful to the baby's body, providing sufficient nutrients for the development and growth of the baby's brain, eyes and heart (APA, 2018). The purpose of this community service is to provide information or knowledge to the public about the importance of giving colostrum and giving exclusive breastfeeding to newborns. This Community Service activity was carried out at Posyandu Flamboyan VI using the Lecture and Question and Answer method regarding colostrum administration and exclusive breastfeeding for newborns to the target group. Counseling was attended by 25 mothers with good knowledge, namely 17 respondents (68%), sufficiently knowledgeable as many as 8 respondents (32%). Counseling about the benefits of colostrum and exclusive breastfeeding is a form of providing information to every mother who has a baby or expectant mother.